Increasing ecological validity in mental fatigue research—A Footbonaut study - Weiler, Helena; Ennigkeit, Fabienne; Spielmann, Jan; Englert, Chris (Frontiers in Psychology, 2025)
IntroductionPast studies have mainly used Stroop tasks to induce mental fatigue in soccer. However, due to the non-sport-specificity of these tasks, their transferability to the real-life effects of mental fatigue in soccer have been questioned. The study's aim was to investigate the effects of two different versions (mentally less vs. mentally more demanding) of a soccer passing task in the so-called Footbonaut on cognitive and soccer-specific performance.MethodsA randomized, counterbalanced experimental within-subjects design was employed (N = 27). We developed two different versions of the soccer passing task in the Footbonaut: a mentally more demanding decision-making and inhibition task in the experimental condition, and a mentally less demanding standard task of the Footbonaut in the control condition.ResultsParticipants showed significantly worse soccer-specific performance in the experimental condition compared to the control condition. No corresponding effects were revealed in cognitive performance.DiscussionThe findings suggest that cognitive-motor interference induced by 30-min Footbonaut technology-based training may induce mental fatigue in soccer players. Future studies should consider developing mentally less-demanding yet comparable control tasks.